Financial Factors Determinant to MSME Performance - Amran Andromeda; Sri Wahyuni; Naelati Tubastuvi; Suryo Budi Santoso (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the factors in financial management that influence the performance of MSMEs in Tegal City/Regency. Methodology/approach: The factors tested include the use of accounting information systems, choice of capital structure, capital budgeting methods, working capital management, and financial technology utilization. The research approach was quantitative, with a population of 880 respondents and 100 samples taken by purposive sampling. Data were obtained using a survey method with a Likert scale questionnaire, which was then analyzed using the Partial Least Square application. Results/findings: The results of the study indicate that in Tegal City and Regency, accounting information systems and capital structure factors have a positive impact on MSME performance, while capital budgeting, working capital, and financial technology have no effect. Conclusions: This study implies that in MSMEs in Tegal City and Regency, the use of better accounting information systems and the selection of an effective capital structure can improve performance. Limitations: Among the many MSME business sectors available, this research only examined 7 (seven) sectors. Contributions: This study contributes to the literature by showing that MSMEs in Tegal City and Regency can improve their performance by using better accounting information systems and selecting an effective capital structure.